An ultrafast self-healing polydimethylsiloxane elastomer with persistent sealing performance. (17th May 2019) - Wang, Da-Peng; Zhao, Zi-Han; Li, Cheng-Hui; Zuo, Jing-Lin
Abstract : A novel polydimethylsiloxane elastomer obtained by crosslinking a long chain of poly(dimethylsiloxane) with tetra-functional biphenyl via an aldimine polycondensation reaction, exhibits ultrafast self-healing capability and persistent sealing performance (can completely self-heal punctured holes or scratches in seconds and therefore maintain its excellent sealing property). Abstract : Silicone waterproofing sealants are susceptible to either rupture or scratches due to their low scratch resistance, leading to reduced sealing performance. Herein, an ultrafast self-healing polydimethylsiloxane elastomer is developed to solve this problem. The novel polydimethylsiloxane elastomer, obtained by crosslinking a long chain of poly(dimethylsiloxane) with a tetra-functional biphenyl unit via an aldimine polycondensation reaction, exhibits ultrafast self-healing properties (can be efficiently healed at room temperature within 60 s) although it is quite tough and strong (with Young's modulus of 120.6 ± 8.2 kPa, elongation >8000%, and adhesive stress values of 30–700 kPa for various substrates). As demonstrated by water absorption tests and self-designed water bag experiments, this new polymer can completely self-heal punctured holes or scratches in seconds and therefore maintain its excellent sealing property. This unique material will have wide commercial applications not only as a sealant, but also in many other industrial fields, including electrochemical sensors, wearable electronics, and biomedical adhesives.